A feasibility study of the use of UmbiFlow™ to assess the impact of heat stress on fetoplacental blood flow in field studies. Issue 2 (10th October 2022) - Bonell, Ana; Vannevel, Valerie; Sonko, Bakary; Mohammed, Nuredin; Vicedo‐Cabrera, Ana M.; Haines, Andy; Maxwell, Neil S.; Hirst, Jane; Prentice, Andrew M.
Abstract: Objective: To evaluate the use of UmbiFlow™ in field settings to assess the impact of heat stress on umbilical artery resistance index (RI). Methods: This feasibility study was conducted in West Kiang, The Gambia, West Africa; a rural area with increasing exposure to extreme heat. We recruited women with singleton fetuses who performed manual tasks (such as farming) during pregnancy to an observational cohort study. The umbilical artery RI was measured at rest, and during and at the end of a typical working shift in women at 28 weeks or more of pregnancy. Adverse pregnancy outcomes (APO) were classified as stillbirth, preterm birth, low birth weight, or small for gestational age, and all other outcomes as normal. Results: A total of 40 participants were included; 23 normal births and 17 APO. Umbilical artery RI demonstrated a nonlinear relationship to heat stress, with indication of a potential threshold value for placental insufficiency at 32°C by universal thermal climate index and 30°C by wet bulb globe temperature. Conclusions: The Umbiflow device proved to be an effective field method for assessing placental function. Dynamic changes in RI may begin to explain the association between extreme heat and APO with an identified threshold of effect. Synopsis: Extreme heat exposure is increasing and a low‐cost umbilical artery Doppler device, UmbiFlow™, can aid understanding of fetoplacental function under heat stress conditions.